Responses to mental health issues among Chinese American Christian communities: report from focus group conversations - Tu, Jennifer Young; Cai, Grace; Lin, Pao-Hwa; Kinghorn, Warren (2023)
Religious and cultural factors play an important part in shaping attitudes about mental health. This study focuses on mental health-related beliefs of a specific ethnocultural population: Chinese American Christians. Using an online adaptation of nominal group technique (NGT), self-identified Chinese American Christians (N = 39) were asked to describe how Christian beliefs/practices and Chinese American identity affect responses to mental health problems, as well as actionable ways for their communities to better support people struggling with mental health issues. Helpful themes included supportive relationships within Christian communities and hope derived from Christian faith. Harmful themes included language and communication barriers, lack of mental health literacy, and stigma attributed by participants to Chinese cultural values. Actionable areas included the cultivation of safe spaces dedicated to open dialogue, integration of Christian belief and psychological perspectives, and general mental health awareness and education.
Keywords: Stigma; Shame; Mental Illness; Mental Health; Christianity; Asian American; Chinese American